HCV‐Positive Donor Organs in Solid Organ Transplantation: "Mind the Gap!". Issue 11 (21st July 2017) - Fishman, J. A.; Forns, X.
Abstract : Transplantation of organs from donors infected with hepatitis C virus presents an opportunity to identify those individuals most likely to benefit from directly active antiviral therapies as well as possible limitations of these therapies in transplant recipients. See the meeting report from Levitsky et al onpage 2790 .